The Influence of Organizational Culture, Leadership, and Work Stress on Employee Performance - Wairisal, Paulus (LifeSciFi, 2023)
This study aims to examine and analyze the influence of organizational culture, leadership, and work stress on employee performance within the Maluku Province Information and Communication Service. The research follows a survey methodology, employing a quantitative analysis approach for data analysis. The study utilizes a census sampling technique, involving a total of 97 respondents. The data is subjected to multiple linear regression for statistical analysis. The results of the quantitative analysis establish several key findings. Organizational culture exhibits a significant positive impact on enhancing employee performance, while leadership also significantly contributes to improved employee performance. On the other hand, work stress demonstrates a notable negative influence on employee performance. For future researchers, it is recommended to consider incorporating additional variables, such as role ambiguity, and applying Structural Equation Modeling (SEM) analysis for a more comprehensive understanding of the relationships.